PENENTUAN BENTUK FUNGSI MODEL EMPIRIK: STUDI KASUS PERMINTAAN KENDARAAN RODA EMPAT BARU - Setyadharma, Andryan (Semarang State University, 2008)
In many cases, the determination of form of the regression function of the empirical model betweenthe linear model and the log-linear model is neglected when someone starts research. Someoneconcludes the best model only by comparing the R2 value from respective function form and determinesthe best form of the function model only based on the highest R2 value. This is clearly wrong. This studyattempted to find the best regression function model by using two kinds of tests: MacKinnon, White andDavidson Test (MWD Test) and Bera and McAleer Test (B-M Test). This Study showed that the twoforms of the empirical function models-both the linear and log-linear functions- could be used to estimatethe demand of the new four wheels vehicle in Indonesia. Furthermore, checking by using classicalassumption, we found that the log-linear function model is the best model to estimate the demand of thenew four wheels vehicle in Indonesia.Keywords: empirical model, linear model, log-linear model